Factors associated with the maintenance of breastfeeding for 6, 12, and 24 months in adolescent mothers - Mariana Muelbert; Elsa R. J. Giugliani (BMC, 2018)
Abstract Background Previous studies have demonstrated that adolescent mothers present a higher risk of not breastfeeding or of early interruption of this practice. Considering the scarcity of studies investigating the determining factors of breastfeeding in adolescent mothers, and the absence of studies exploring the determining factors of breastfeeding maintenance for different periods of time in a single population of adolescent mothers, the aim of this research was to identify factors associated with breastfeeding maintenance for at least 6, 12, and 24 months in adolescent mothers. Methods Data analysis from a randomised control trial involving adolescent mothers recruited at a university hospital in southern Brazil. Participants were followed through the first year of life of their infants and reassessed at 4-7 years. Factors associated with any breastfeeding for at least 6, 12, and 24 months were assessed using multivariate Poisson regression. Results Data for 228, 237, and 207 mothers were available, respectively. Breastfeeding maintenance for at least 6, 12, and 24 months was observed in 68.4, 47.3, and 31.9% of the sample, respectively. Only one factor was associated with breastfeeding maintenance at all outcomes: infant not using a pacifier showed a higher probability of breastfeeding maintenance in the first 2 years. Maternal grandmother breastfeeding support and exclusive breastfeeding duration were associated with breastfeeding maintenance for 6 and 12 months. The other factors evaluated were associated with breastfeeding maintenance at only one of the time points assessed: 6 months, maternal skin color (black/brown); 12 months, female infant and partner breastfeeding support; and 24 months, older paternal age and multiparity. Conclusions The present findings shed light upon barriers and facilitators of breastfeeding practices among adolescent mothers. In order to contribute to the challenge of increasing BF duration among adolescent mothers interventions aimed at boosting breastfeeding maintenance among this population should take into consideration the determining factors here identified. Additionally, breastfeeding education and support should be provided continuously as factors influencing these practices vary with time. Thus, support for adolescent mothers during the different stages of breastfeeding need to be tailored to have a positive impact on breastfeeding experience.